Hepatic Glucagon Action Is Essential for Exercise-Induced Reversal of Mouse Fatty Liver - Berglund, Eric D. (American Diabetes Association, 2011)
OBJECTIVE: Exercise is an effective intervention to treat fatty liver. However, the mechanism(s) that underlie exercise-induced reductions in fatty liver are unclear. Here we tested the hypothesis that exercise requires hepatic glucagon action to reduce fatty liver. RESEARCH DESIGN AND METHODS: C57BL/6 mice were fed high-fat diet (HFD) and assessed using magnetic resonance, biochemical, and histological techniques to establish a timeline for fatty liver development over 20 weeks. Glucagon receptor null (gcgr(−/−)) and wild-type (gcgr(+/+)) littermate mice were subsequently fed HFD to provoke moderate fatty liver and then performed either 10 or 6 weeks of running wheel or treadmill exercise, respectively. RESULTS: Exercise reverses progression of HFD-induced fatty liver in gcgr(+/+) mice. Remarkably, such changes are absent in gcgr(−/−) mice, thus confirming the hypothesis that exercise-stimulated hepatic glucagon receptor activation is critical to reduce HFD-induced fatty liver. CONCLUSIONS: These findings suggest that therapies that use antagonism of hepatic glucagon action to reduce blood glucose may interfere with the ability of exercise and perhaps other interventions to positively affect fatty liver.